Pervasiveness and characteristics of microplastics in surface water and sediment of the Buriganga River, Bangladesh. (November 2022) - Islam, Muhammad Saiful; Islam, Zahidul; Hasan, Md. Rashed
Abstract: Microplastics (MPs) are an emerging environmental problem due to their all-around existence and extraordinary stability. A significant number of studies are found in recent literature on the occurrence, distribution, transport, and fate of the MPs in several environmental compartments. In this study, we have investigated the occurrence and characteristics of MPs in the surface water and sediment of the Buriganga river, located beside the mega-city of Dhaka in Bangladesh. In the Buriganga river, the concentration of MPs in the surface water was found from 4.33 ± 0.58 to 43.67 ± 0.58 items L −1, and in the sediment, MPs varied from 17.33 ± 1.53 to 133.67 ± 5.51 items kg −1 of dry sediment. Fragment-type MPs were predominant in the surface water and sediment, which was 72.7% and 85.5% respectively. The most abundant polymer type polypropylene (PP) was found -to be 46% in the surface water and 61% in the sediment sample. The next major category, polyethylene (PE) was found to be 26% and 21%, respectively. Polystyrene (PS), polyvinyl chloride (PVC), polyethylene terephthalate (PET), and polyamide (PA) were other commonly detected polymer types. The MPs were found to be contaminated by Pb, Cd, Cr, Zn, Cu, and Sn from Energy dispersive-X-ray fluorescence (ED-XRF) analysis. Tannery-induced Cr was detected in the highest concentrations in the MPs, which were 20.67 ± 1.66 mg kg −1 (in surface water) and 14.2 ± 1.25 mg kg −1 (in sediment). The pollution load index (PLI) of the MPs contamination in different sampling sites along the Buriganga river was found in the risk level category of I and II. The anthropogenic influence of the city area was reflected in the PLI values, which had an increasing trend from the upstream sampling points (1.00 ± 1.00, 1.00 ± 1.00) to the downstream sites (10.09 ± 1.00, 7.71 ± 3.60). Graphical abstract: Microplastics from surface water and sediment of the Buriganga River and their physical-chemical features. Image 1 Highlights: Microplastics were detected in each surface water and sediment sample of the Buriganga River. Fragment-shaped polypropylene (PP) and polyethylene (PE) were the predominant polymer types. Microplastics were found to be contaminated by heavy metals, such as Pb, Cd, Cr, Cu, Zn, and Sn. Plastic recycling and molding industries were the major sources of microplastics in the Buriganga River.